2017
DOI: 10.3892/mmr.2017.8228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of abnormal nuclear and mitochondrial genes in esophageal cancer cells

Abstract: The present study aimed to detect the mutation characteristics of mitochondrial DNA (mtDNA) in Eca109 of Ec9706 cells, and to investigate their association with the nuclear genome (nDNA), thus providing a basis for gene targeting therapies for esophageal squamous cell carcinoma (ESCC). In vitro-cultured Ec9706 and Eca109 cells were analyzed the changes of single-nucleotide polymorphisms (SNPs), insertions/deletions (INDELs), copy number variation, and structure variation (SV) of their genome by high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Heterozygous germline ACAD9 mutations are associated with severe, isolated complex I deficiency and cardiac myopathy [ 56 , 57 ]. However, recent publications suggest possible roles for ACAD9 in several cancers, such as prostate [ 58 ] and esophageal cancer [ 59 ]. In addition, Roberts et al [ 10 ] reported a premature truncating variant in the ACAD9 gene in one of 38 FPC kindreds (2.6%), among other more frequently mutated genes such as BRCA2 and ATM .…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous germline ACAD9 mutations are associated with severe, isolated complex I deficiency and cardiac myopathy [ 56 , 57 ]. However, recent publications suggest possible roles for ACAD9 in several cancers, such as prostate [ 58 ] and esophageal cancer [ 59 ]. In addition, Roberts et al [ 10 ] reported a premature truncating variant in the ACAD9 gene in one of 38 FPC kindreds (2.6%), among other more frequently mutated genes such as BRCA2 and ATM .…”
Section: Discussionmentioning
confidence: 99%